MANIPULATIVE LEARNING MEDIA BASED ON STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) TO IMPROVE STUDENT LEARNING OUTCOMES - Sulistyawati, Eka; Puspitasari, Diana; Saidah, Zulinda Nur; Rofiqoh, Iffatur (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study aimed to develop manipulative learning media based on STEM (Science, Technology, Engineering, and Mathematics) called Magic Hours on Clock and Corner material. Research and development model used by using the procedure of Analysis, Design, Development, Implementation, and Evaluation (ADDIE). The population of this study was all 4th grade students from elementary school in Kediri. Due to the Covid-19 Pandemic situation and study from home policy, manipulative media was tested on 13 fourth grade elementary school students in Kediri who came from the same village to reduce students' mobility from one place to another. Data collection techniques are collecting through expert validation, teacher questionnaires, student questionnaires, test, observation, and interviews. The instruments are test (description questions) and non-test instruments (material validation sheets, design validation sheets, practicality assessment sheets, questionnaire validation sheet, and questionnaires). The result shows that the learning media are valid, practical, and effective. Learning media have feasible criteria with an assessment score of 88.46% from media experts and 86.67% from material experts. In the practicality test, learning media obtained a percentage of 86.67% with practical criteria. The result of a one-sample t-test on student test scores indicates that the average mathematics score test is significantly more than Minimum Completeness Criteria.